The relationship between cardiac surgeon experience and average patient risk profile: CA and NY statewide analysis. Issue 4 (19th January 2021) - Weininger, Gabe; Einarsson, Arnar; Mori, Makoto; Brooks, Cornell; Shang, Michael; Assi, Roland; Vallabhajosyula, Prashanth; Geirsson, Arnar
Abstract: Background: It is unknown how high and low‐risk cases are distributed among cardiac surgeons of different experience levels. The purpose of this study was to determine if high and low‐risk coronary artery bypass grafting (CABG) cases are distributed among surgeons in such a way that would optimize outcomes in light of recent studies that show mid‐career surgeons may obtain better patient outcomes on more complex cases. Methods: We performed a cross‐sectional study using aggregated New York (NY) and California (CA) statewide surgeon‐level outcome data, including 336 cardiac surgeons who performed 43, 604 CABGs. The surgeon observed and expected mortality rates (OMR and EMR) were collected and the number of years‐in‐practice was determined by searching for surgeon training history on online registries. Loess and linear regression models were used to characterize the relationship between surgeon EMR and surgeon years‐in‐practice. Results: The median number of surgeon years‐in‐practice was 20 (interquartile range [IQR] 11–28) with a median annual case volume of 46 (IQR 19, 70.25). The median surgeon observed to expected mortality (O:E) ratio was 0.87 (IQR 0.19–1.4). Median EMR for CA surgeons was 2.42% and 1.44% for NY surgeons. Linear regression models showed EMR was similar across years in practice. Regression models also showed surgeon O:E ratios were similar across years‐in‐practice. Conclusion: High and low‐risk CABG cases are relatively equally distributed among surgeons of differing experience levels. This equal distribution of high and low‐risk cases does not reflect a triaging of more complex cases to more experienced surgeons, which prior research shows may optimize patient outcomes.